Solar Rooftop PV Power Generation for a Commercial Building in Thailand - Sommani, Piyanart; Nookwan, Jiraporn; Lothongkum, Anchaleeporn Waritswat (My University, 2023)
Solar energy is significant potential for power and heat production. The Alternative Energy Development Plan 2018–2037 (AEDP2018) developing by Thailand’s Ministry of Energy demonstrates that solar energy is a key role in renewable energy utilization, especially for power generation. In general, solar photovoltaic (PV) technology is the most common type of solar power generation technology. This paper presented a potential of using grid-connected solar PV power generation system for the rooftop of a commercial building. The design and simulation of the solar rooftop PV power generation system and the economic analysis were accomplished. The installation of 1.85 MWp grid-connected solar PV power generation system on the rooftop area required 3,440 pieces of 540 Wp solar panels. By using PVsyst version 7.2, the solar panel configuration was connected in 20 pieces/string in series and 172 strings in parallel, with 80 kWac string inverters of 18 units. The simulated results of produced energy, specific production, and performance ratio were 2,678 MWh/year, 1,442 kWh/kWp/year, and 80% respectively. As a result, the energy cost saving was 269,317 USD with payback period (PB), net present value (NPV), and internal rate of return (IRR) of 6.37 years, 1,062,430 USD, and 15%, respectively. In conclusion, the installation of 1.85 MWp solar rooftop PV power generation system is technically feasible for the investment.
Keywords: Commercial building; PVsyst; Solar rooftop